Sodium-ion battery positive electrode material precursor as well as preparation method and application thereof

By using Co-doped YTiTaO6 composite SrRuO3 coating on the positive electrode material of sodium ion battery, the problems of insufficient conductivity and structural instability are solved, the electrochemical performance and stability of sodium ion battery are significantly improved, and the battery is extended Service life.

CN119306265AActive Publication Date: 2025-01-14PAWA (ZHUJI) NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411832995.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-14
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode material has insufficient conductivity, unstable structure and poor corrosion resistance, resulting in low specific capacity, poor cycle stability and short service life.

Method used

Using Co-doped YTiTaO6 composite SrRuO3 material as the cladding layer, the Co-doped YTiTaO6 and SrRuO3 cladding layers are formed on the surface of the layered hydroxide precursor to improve the conductivity and structural stability, and form an effective conductive network to Improve battery performance.

Benefits of technology

It significantly improves the electrochemical performance and stability of sodium ion batteries, extends the service life of the battery, and improves the cycle stability and discharge specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306265A_ABST
    Figure CN119306265A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material precursor and a preparation method and application thereof. The sodium ion battery positive electrode material precursor comprises a layered hydroxide precursor and a coating layer coating at least part of the surface of the layered hydroxide precursor; wherein the coating layer is made of a Co-doped YTiTaO6 material or a Co-doped YTiTaO6 and SrRuO3 composite material, and the coating layer is made of a Co-doped YTiTaO6 and SrRuO3 composite material. According to the invention, Co is used for doping the YTiTaO6 material; by doping Co, more free electrons can be introduced into crystal lattices under the condition that the crystal structure of the YTiTaO6 is not damaged, so that the conductivity of the YTiTaO6 is remarkably improved; therefore, when the Co-doped YTiTaO6 material is used as the coating layer of the precursor of the positive electrode material of the sodium-ion battery, the electrochemical performance of the sodium-ion battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material precursor and a preparation method and application thereof. Background Art

[0002] In the field of energy storage, sodium-ion batteries have gradually become an important alternative to lithium-ion batteries due to their abundant raw materials, low cost and environmental friendliness. The positive electrode material of sodium-ion batteries is a key factor affecting battery performance. At present, the commonly used positive electrode materials for sodium-ion batteries mainly include layered oxides, polyanion compounds and Prussian blue compounds. Among them, layered oxides are the most studied type of positive electrode materials for sodium-ion batteries due to their simple synthesis and excellent performance. However, existing layered oxide materials generally have problems such as insufficient conductivity, unstable structure, and poor corrosion resistance, which leads to the defects of low specific capacity, poor cycle stability, and short service life of the sodium-ion batteries prepared therefrom. Summary of the invention

[0003] The purpose of the present invention is to provide a sodium ion battery positive electrode material precursor with good conductivity and stable structure, and a preparation method and application thereof.

[0004] In the first aspect, the present invention provides a sodium ion battery positive electrode material precursor, which adopts the following technical solution: A sodium ion battery positive electrode material precursor comprises a layered hydroxide precursor and a coating layer coated on at least a portion of the surface of the layered hydroxide precursor; wherein the coating layer is a Co-doped YTiTaO6 material or a Co-doped YTiTaO6 composite SrRuO3 material.

[0005] Preferably, in the Co-doped YTiTaO6, the molar ratio of Y, Ti, Co and Ta is 1:1-0.75x:x:1, 0.01≤x≤0.1.

[0006] Preferably, in the Co-doped YTiTaO6 composite SrRuO3 material, the mass ratio of Co-doped YTiTaO6 to SrRuO3 is (1~3):(1~3).

[0007] Preferably, the mass of the coating layer is 1-20% of the mass of the layered hydroxide precursor.

[0008] Preferably, the layered hydroxide precursor is one of nickel-iron-copper-manganese layered hydroxide, copper-iron-manganese layered hydroxide, nickel-manganese-copper layered hydroxide, and nickel-zinc-iron-manganese layered hydroxide.

[0009] More preferably, the layered hydroxide is nickel-iron-manganese layered hydroxide or copper-iron-manganese layered hydroxide. Further preferably, the layered hydroxide precursor is Ni x Fe y Mn z (OH)2, 0.3≤x≤0.8, 0<y≤0.4, 0<z≤0.4, x+y+z=1; or Cu a Fe b Mn c (OH)2, 0.1≤a≤0.5, 0≤b≤0.4, 0≤c≤0.6, a+b+c=1.

[0010] In a second aspect, the present invention provides a method for preparing a precursor of a positive electrode material for a sodium ion battery, comprising the following steps: S1: adding yttrium source, titanium source, cobalt source, tantalum source and complexing agent into water, stirring evenly, heating and evaporating to dryness, and further drying to obtain powder; pre-burning the powder, and then heating and calcining to obtain Co-doped YTiTaO6 powder; S2: Dispersing Co-doped YTiTaO6 powder or a mixed powder consisting of Co-doped YTiTaO6 powder and SrRuO3 powder in an alcohol solvent to obtain a dispersion; dispersing a layered hydroxide precursor in the dispersion, stirring and evaporating to obtain a solid; after the solid is dried, heating and then keeping warm under a protective atmosphere to obtain a precursor of a positive electrode material for a sodium ion battery.

[0011] Preferably, in step S1, the yttrium source is one or more of yttrium nitrate, yttrium chloride, and yttrium acetate; The titanium source is one or more of butyl titanate, titanium nitrate, titanium sulfate, and titanyl sulfate; The cobalt source is one or more of cobalt nitrate, cobalt sulfate, cobalt chloride and cobalt acetate; The tantalum source is one or more of ethoxy tantalum, ammonium tantalate, and sodium tantalate; The yttrium source, titanium source, cobalt source and tantalum source are added according to the molar ratio of Y, Ti, Co and Ta being 1:1-0.75x:x:1, 0.01≤x≤0.1.

[0012] Preferably, in step S1, the complexing agent is one or more of citric acid, urea, and polyethylene glycol, and the ratio of the molar number of the complexing agent to the total molar number of Y, Ti, Co, and Ta ions in the yttrium source, titanium source, cobalt source, and tantalum source is 1-2:1.

[0013] Preferably, in step S1, the heating evaporation temperature is 80-100° C.; the drying temperature is 80-150° C., and the drying time is 8-12 hours.

[0014] Preferably, in step S1, the pre-sintering temperature is 400-600° C., and the pre-sintering time is 5-8 hours; the calcining temperature is 900-1300° C., and the calcining time is 8-12 hours.

[0015] Preferably, in step S2, the amount of Co-doped YTiTaO6 powder added is 1-10 wt% of the amount of layered hydroxide precursor added; the amount of SrRuO3 powder added is 1-10 wt% of the amount of layered hydroxide precursor added.

[0016] Preferably, in step S2, the alcohol solvent is anhydrous ethanol.

[0017] Preferably, in step S2, the stirring evaporation temperature is 80-150° C.; the drying temperature is 100-120° C.; and the drying time is 8-12 hours.

[0018] Preferably, in step S2, the insulation temperature is 200-400° C., and the insulation time is 0.5-5 h.

[0019] In a third aspect, the present invention provides a sodium ion battery positive electrode material, which is obtained by mixing the aforementioned sodium ion battery positive electrode material precursor with a sodium source and then sintering.

[0020] Preferably, the sodium source is one or more of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium acetate, and sodium oxalate, more preferably sodium carbonate.

[0021] Preferably, the mixing ratio of the sodium ion battery positive electrode material precursor and the sodium source is 1 to 1.1.

[0022] The sodium mixing ratio is the ratio of the molar number of Na to the total molar number of metal elements in the precursor of the positive electrode material of the sodium ion battery; that is, if the precursor of the positive electrode material of the sodium ion battery is Ni x Fe y Mn z (OH)2, the sodium mixing ratio is the ratio of the molar number of Na to the total molar number of Ni, Fe and Mn.

[0023] Preferably, the sintering temperature is 700-950° C., and the sintering time is 15-28 hours.

[0024] In a fourth aspect, the present invention provides a sodium ion battery, comprising the aforementioned sodium ion battery positive electrode material.

[0025] Beneficial effects of the present invention: 1) YTiTaO6 has excellent structural stability and corrosion resistance. Coating it on the sodium-electrochemical material precursor can reduce the decomposition and structural damage of the positive electrode material during the cycle and prevent the positive electrode material from being corroded by the electrolyte. However, YTiTaO6 has low conductivity, so when it is used as a coating layer for the precursor of the positive electrode material of a sodium-ion battery, the improvement in the electrochemical performance of the sodium-ion battery is very limited. In the present invention, Co is used to dope the YTiTaO6 material; Co doping can introduce more free electrons into the lattice without destroying the YTiTaO6 crystal structure, thereby significantly improving the conductivity of YTiTaO6; therefore, when the Co-doped YTiTaO6 material is used as a coating layer for the precursor of the positive electrode material of a sodium-ion battery, the electrochemical performance of the sodium-ion battery can be effectively improved.

[0026] 2) The Co-doped YTiTaO6 composite SrRuO3 material is used as the coating layer of the precursor of the positive electrode material of the sodium ion battery in the present invention, mainly because the Co-doped YTiTaO6 has excellent conductivity and structural stability, which can significantly improve the overall conductivity of the battery material, and SrRuO3 can be used as a conductive reinforcement layer to further optimize the electronic conductivity of the battery, form an effective conductive network, promote the rapid migration of sodium ions, and provide a stable reaction interface, thereby improving the stability of the sodium ion battery and its electrochemical performance as a whole. Compared with a single YTiTaO6 or SrRuO3 material, the composite coating solves the problem of insufficient electrochemical activity that may exist in a single coating.

[0027] 3) The Co-doped YTiTaO6 composite SrRuO3 material of the present invention can form a good bonding interface with the layered hydroxide precursor during the heat treatment process, avoiding the common phase separation problem and ensuring the stability of the positive electrode material during the charge and discharge process. Therefore, the synergistic effect of Co-doped YTiTaO6 and SrRuO3 in the Co-doped YTiTaO6 composite SrRuO3 material can significantly improve the overall performance of sodium ion batteries and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Example 1 SEM image of the prepared positive electrode material.

[0029] Figure 2 The electrochemical performance diagram of the battery assembled with the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3.

[0030] Figure 3 This is the electrochemical performance diagram of the battery assembled with the positive electrode materials prepared in Examples 5 to 8.

[0031] Figure 4Electrochemical performance diagram of batteries assembled from the positive electrode materials prepared in Example 1, Example 9 and Example 10. DETAILED DESCRIPTION

[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0033] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0034] Preparation Example 1 Preparation of Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 Add pure water to the reactor to 1 / 2 of the volume, then introduce 6.5g / L ammonia water as a complexing agent and 4.5mol / L sodium hydroxide as a precipitant to form a bottom liquid with a pH of 12, and then introduce nitrogen to keep the oxygen concentration in the reactor below 0.5%. Nickel sulfate hexahydrate, ferrous sulfate heptahydrate, and manganese sulfate tetrahydrate were weighed and dissolved in water according to the Ni:Fe:Mn molar ratio of 1:1:1. The total metal ion concentration was 3.6mol / L to obtain a metal salt solution. The metal salt solution, 4.5mol / L sodium hydroxide, and 6.5g / L ammonia water were passed into the reactor for co-precipitation reaction. The reaction was stopped when the synthetic particle size was 5μm. The temperature of the entire reaction process was controlled at 60°C, the pH was 11-12, and the stirring rate was 500rpm. The precursor slurry after the reaction was filtered, washed, and dried at 130°C for 10h to obtain Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2.

[0035] Preparation Example 2 Preparation of Cu 0.2 Fe 0.3 Mn 0.5 (OH)2 Add pure water to the reactor to 1 / 2 of the volume, then introduce 6.5g / L ammonia water as a complexing agent and 4.5mol / L sodium hydroxide as a precipitant to form a bottom solution with a pH of 11, and then introduce nitrogen to keep the oxygen concentration in the reactor below 0.5%. Copper sulfate, iron sulfate, and manganese sulfate are weighed and dissolved in water according to a Cu:Fe:Mn molar ratio of 0.2:0.3:0.5, and the total metal ion concentration is 3.0mol / L to obtain a metal salt solution. The metal salt solution, 4.5mol / L sodium hydroxide, and 6.5g / L ammonia water are passed into the reactor for co-precipitation reaction. The reaction is stopped when the synthetic particle size is 5μm; the temperature of the entire reaction process is controlled at 60°C, the pH is 11-12, and the stirring rate is 350rpm. The precursor slurry after the reaction is filtered, washed, and dried at 130°C for 12h to obtain the preparation of Cu 0.2 Fe 0.3 Mn 0.5 (OH)2.

[0036] Example 1 In this embodiment, the layered hydroxide precursor in the precursor of the positive electrode material of the sodium ion battery is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Co-doped YTiTaO6 composite SrRuO3 material.

[0037] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: S1: Yttrium nitrate, butyl titanate, cobalt nitrate, ethoxytantalum and citric acid are stirred and mixed in water to obtain a mixed solution, wherein: yttrium nitrate, butyl titanate, cobalt nitrate and ethoxytantalum are added according to the molar ratio of Y, Ti, Co and Ta of 1:0.97:0.04:1; the ratio of the molar number of citric acid to the total molar number of Y, Ti, Co and Ta in yttrium nitrate, butyl titanate, cobalt nitrate and ethoxytantalum is 1.4:1. The mixed solution is stirred and evaporated to dryness at 120°C, and dried at 130°C for 10h to obtain a powder, and then the powder is placed in a muffle furnace for pre-calcination at 500°C for 6h, and then the temperature is raised to 1200°C and calcined for 12h; Co-doped YTiTaO6 powder is obtained.

[0038] S2: Add the Co-doped YTiTaO6 powder and SrRuO3 powder prepared in step S1 into anhydrous ethanol, stir with ultrasound for 2 hours to obtain a dispersion; add the Ni prepared in Preparation Example 1 into the dispersion. 1 / 3 Fe 1 / 3 Mn 1 / 3(OH)2, continue stirring and ultrasonic for 3h, then evaporate to dryness with stirring at 120℃, and dry in an oven at 150℃ for 10h to obtain a solid, heat the solid to 300℃ under a protective atmosphere and keep it warm for 4h to obtain a Co-doped YTiTaO6 composite SrRuO3-coated sodium positive electrode material precursor. Among them: the amount of Co-doped YTiTaO6 powder added and the amount of SrRuO3 powder added are Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added at 5wt%.

[0039] Preparation of positive electrode materials for sodium ion batteries: Co-doped YTiTaO6 composite SrRuO3-coated sodium electric positive electrode material precursor and anhydrous sodium carbonate were mixed evenly according to a sodium mixing ratio of 1.05, and then sintered in a muffle furnace at 900°C for 20h to obtain the positive electrode material Co-doped YTiTaO6 composite SrRuO3-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0040] The SEM image of the positive electrode material prepared in this embodiment is as follows: Figure 1 As shown, the primary particles of the positive electrode material are flake-shaped and spherical as a whole, and the coating layer is tightly coated on the surface of the material without agglomeration.

[0041] Example 2 The method is basically the same as Example 1, except that the coating layer is Co-doped YTiTaO6 and does not contain SrRuO3; that is, SrRuO3 powder is not added in step (2), and the amount of Co-doped YTiTaO6 powder added is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The amount of (OH)2 added was 10wt%; the prepared precursor was: Co-doped YTiTaO6 coated Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is Co-doped YTiTaO6 coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0042] Comparative Example 1 Directly use the Ni prepared in Preparation Example 1 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 was used as a precursor without coating; according to the preparation method of the positive electrode material for sodium ion battery in Example 1, the precursor was mixed with sodium carbonate and sintered to prepare the positive electrode material NaNi 1 / 3 Fe1 / 3 Mn 1 / 3 O2.

[0043] Comparative Example 2 The difference from Example 2 is that the coating layer is YTiTaO6; the preparation method of the corresponding YTiTaO6 is as follows: Yttrium nitrate, butyl titanate, ethoxytantalum and citric acid are stirred and mixed in water to obtain a mixed solution, wherein: yttrium nitrate, butyl titanate and ethoxytantalum are added according to the molar ratio of Y, Ti and Ta of 1:1:1; the ratio of the molar number of citric acid to the total molar number of Y, Ti and Ta in yttrium nitrate, butyl titanate and ethoxytantalum is 1.4:1. The mixed solution is stirred and evaporated to dryness at 120°C, and dried at 130°C for 10h to obtain a powder, and then the powder is placed in a muffle furnace for pre-calcination at 500°C for 6h, and then heated to 1200°C for calcination for 12h; YTiTaO6 powder is obtained. The dried powder is placed in a muffle furnace for calcination at 800°C for 15h to obtain YTiTaO6 powder.

[0044] The rest of the preparation method is the same as in Example 2, and the corresponding precursor prepared is Ni coated with YTiTaO6. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is NaNi coated with YTiTaO6 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0045] Comparative Example 3 The method is basically the same as Example 1, except that SrRuO3 is directly used as the coating layer; that is, Co-doped YTiTaO6 powder is not added in step (2), and the amount of SrRuO3 powder added is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The amount of (OH)2 added was 10wt%; the corresponding precursor was SrRuO3-coated Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, the positive electrode material is SrRuO3 coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2.

[0046] Example 3 It is basically the same as Example 1, except that, during the preparation of Co-doped YTiTaO6 powder, yttrium nitrate, butyl titanate, cobalt nitrate and tantalum ethoxide are added according to the molar ratio of Y, Ti, Co and Ta of 1:0.9925:0.01:1.

[0047] Example 4 It is basically the same as Example 1, except that, during the preparation of Co-doped YTiTaO6 powder, yttrium nitrate, butyl titanate, cobalt nitrate and ethoxytantalum are added according to the molar ratio of Y, Ti, Co and Ta of 1:0.925:0.1:1.

[0048] Example 5 The same as Example 1, except that the layered hydroxide precursor is Cu prepared in Preparation Example 2. 0.2 Fe 0.3 Mn 0.5 (OH)2, the prepared precursor is: Co-doped YTiTaO6 composite SrRuO3 coated Cu 0.2 Fe 0.3 Mn 0.5 (OH)2, the positive electrode material is Co-doped YTiTaO6 composite SrRuO3 coated NaCu 0.2 Fe 0.3 Mn 0.5 O2.

[0049] Example 6 The method is basically the same as Example 5, except that the coating layer is Co-doped YTiTaO6 and does not contain SrRuO3; that is, SrRuO3 powder is not added in step (2), and the amount of Co-doped YTiTaO6 powder added is Cu 0.2 Fe 0.3 Mn 0.5 The amount of (OH)2 added was 10wt%; the prepared precursor was: Co-doped YTiTaO6 coated Cu 0.2 Fe 0.3 Mn 0.5 (OH)2, the positive electrode material is Co-doped YTiTaO6 coated NaCu 0.2 Fe 0.3 Mn 0.5 O2.

[0050] Example 7 The same as Example 5, except that the amount of Co-doped YTiTaO6 powder added is Cu 0.2 Fe 0.3 Mn 0.5 The amount of (OH)2 added was 7.5wt%, and the amount of SrRuO3 powder added was Cu 0.2 Fe 0.3 Mn 0.5 (OH)2 added amount is 2.5wt%.

[0051] Example 8 The same as Example 5, except that the amount of Co-doped YTiTaO6 powder added is Cu 0.2 Fe 0.3 Mn 0.5 The amount of (OH)2 added was 2.5wt%, and the amount of SrRuO3 powder added was Cu 0.2 Fe 0.3 Mn 0.5 (OH)2 added amount is 7.5wt%.

[0052] Example 9 In this embodiment, the layered hydroxide precursor in the precursor of the positive electrode material of the sodium ion battery is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Co-doped YTiTaO6 composite SrRuO3 material.

[0053] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: S1: Stir and mix yttrium chloride, titanium sulfate, cobalt chloride, ammonium tantalate and urea in water to obtain a mixed solution, wherein: yttrium chloride, titanium sulfate, cobalt chloride and ammonium tantalate are added according to the molar ratio of Y, Ti, Co and Ta of 1:0.955:0.06:1; the ratio of the molar number of urea to the total molar number of Y, Ti, Co and Ta in yttrium chloride, titanium sulfate, cobalt chloride and ammonium tantalate is 1.1:1. Stir and evaporate the mixed solution at 120°C, and dry it at 130°C for 10h to obtain a powder, then pre-calculate the powder at 400°C in a muffle furnace for 8h, and then heat it to 900°C and calcine it for 16h; obtain Co-doped YTiTaO6 powder.

[0054] S2: Add the Co-doped YTiTaO6 powder and SrRuO3 powder prepared in step S1 into anhydrous ethanol, stir and ultrasonicate for 1.5 hours to obtain a dispersion; add the Ni prepared in Preparation Example 1 into the dispersion. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, continue stirring and ultrasonic for 2h, then evaporate to dryness with stirring at 120℃, and dry in an oven at 150℃ for 10h to obtain a solid, heat the solid to 400℃ under a protective atmosphere and keep it warm for 4h to obtain a Co-doped YTiTaO6 composite SrRuO3-coated sodium positive electrode material precursor. Among them: the amount of Co-doped YTiTaO6 powder added and the amount of SrRuO3 powder added are Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount is 2wt%.

[0055] Preparation of positive electrode materials for sodium ion batteries: Co-doped YTiTaO6 composite SrRuO3-coated sodium electric positive electrode material precursor and anhydrous sodium carbonate were mixed evenly according to a sodium mixing ratio of 1.1, and then sintered in a muffle furnace at 800°C for 22h to obtain the positive electrode material Co-doped YTiTaO6 composite SrRuO3-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0056] Example 10 In this embodiment, the layered hydroxide precursor in the precursor of the positive electrode material of the sodium ion battery is Ni prepared in Preparation Example 1. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2; the coating layer is Co-doped YTiTaO6 composite SrRuO3 material.

[0057] The method for preparing a precursor of a positive electrode material for a sodium ion battery in this embodiment comprises the following steps: S1: Yttrium acetate, titanyl sulfate, cobalt acetate, sodium tantalate and citric acid are stirred and mixed in water to obtain a mixed solution, wherein: yttrium acetate, titanyl sulfate, cobalt acetate and sodium tantalate are added according to the molar ratio of Y, Ti, Co and Ta of 1:0.94:0.08:1; the ratio of the molar number of citric acid to the total molar number of Y, Ti, Co and Ta in yttrium acetate, titanyl sulfate, cobalt acetate and sodium tantalate is 1.7:1. The mixed solution is stirred and evaporated to dryness at 120°C, and dried at 150°C for 8h to obtain a powder, and then the powder is placed in a muffle furnace for pre-calcination at 600°C for 5h, and then the temperature is raised to 1300°C and calcined for 8h; Co-doped YTiTaO6 powder is obtained.

[0058] S2: Add the Co-doped YTiTaO6 powder and SrRuO3 powder prepared in step S1 into anhydrous ethanol, stir and ultrasonicate for 1.0 h to obtain a dispersion; add the Ni prepared in Preparation Example 1 into the dispersion. 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2, continue stirring and ultrasonic for 4 hours, then evaporate to dryness with stirring at 120℃, and dry in an oven at 150℃ for 10 hours to obtain a solid, heat the solid to 200℃ under a protective atmosphere and keep it warm for 5 hours to obtain a Co-doped YTiTaO6 composite SrRuO3-coated sodium positive electrode material precursor. Among them: the amount of Co-doped YTiTaO6 powder added and the amount of SrRuO3 powder added are Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 added amount is 8wt%.

[0059] Preparation of positive electrode materials for sodium ion batteries: Co-doped YTiTaO6 composite SrRuO3-coated sodium electric positive electrode material precursor and anhydrous sodium carbonate were mixed evenly according to a sodium mixing ratio of 1.05, and then sintered in a muffle furnace at 950°C for 18 hours to obtain the positive electrode material Co-doped YTiTaO6 composite SrRuO3-coated NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0060] The positive electrode materials obtained in Examples 1 to 10 and Comparative Examples 1 to 3 were assembled into a battery. The positive electrode material: conductive graphite: PVDF mass ratio was 8:1:1, and then the mixture was weighed and ground. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added and continued to be ground and stirred to form a uniform slurry. The slurry was evenly coated on an aluminum foil with a coating thickness of 200 μm, and placed in a drying oven at 90°C for 10 hours, and then cut into discs with a diameter of 12 mm. The disc was used as the positive electrode, the sodium sheet was used as the negative electrode, the electrolyte included a solvent and NaPF6, wherein the NaPF6 concentration was 1 mol / L, and the solvent of the electrolyte was a mixed solvent of EC, DEC and DMC with a volume ratio of 1:1:1. The battery was assembled in a glove box in the order of button-type battery assembly.

[0061] The assembled batteries were subjected to performance testing. The assembled batteries that had been left to stand overnight were placed in a LAND2001CT battery test box for charge and discharge testing. The test was conducted at 25°C, 1C, and a cycle voltage of 2-4V for 50 cycles.

[0062] Figure 2 The data graph of the cycle stability and discharge specific capacity of the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 after being assembled into batteries. It can be seen from the figure that compared with the battery assembled with the positive electrode material in Comparative Example 1, the cycle stability and discharge specific capacity of the battery assembled with the coated modified positive electrode material are improved to a certain extent; the positive electrode material prepared in Example 2 has a further improvement in cycle stability and discharge specific capacity compared with the positive electrode material without Co-doped YTiTaO6 coating layer in Comparative Example 2. The positive electrode material of Co-doped YTiTaO6 composite SrRuO3 as the coating layer in Example 1 has a significant improvement in cycle stability and discharge specific capacity compared with the positive electrode material with Co-doped YTiTaO6 as the coating layer (Example 2) and the positive electrode material with SrRuO3 as the coating layer (Comparative Example 3). In Examples 3 and 4, the doping amount of Co is mainly changed, and its performance will fluctuate to a certain extent compared with Example 1, but it still has good cycle stability and discharge specific capacity.

[0063] Figure 3The data of the cycle stability and discharge specific capacity of the positive electrode materials prepared in Examples 5 to 8 after being assembled into batteries are shown in the figure. It can be seen from the figure that when the positive electrode active material is NaCu 0.2 Fe 0.3 Mn 0.5 O2, using Co-doped YTiTaO6 composite SrRuO3 as the coating layer, its cycle stability and discharge specific capacity are still improved compared with the positive electrode material coated with Co-doped YTiTaO6 (Example 6). In Example 7 and Example 8, the ratio of Co-doped YTiTaO6 powder and SrRuO3 powder in the coating layer is adjusted. It can be seen that when the content ratio of Co-doped YTiTaO6 powder in Example 7 increases, its performance will be slightly reduced compared with Example 5. When the content ratio of SrRuO3 powder in Example 8 increases, its performance will also be reduced to a certain extent; but overall, Example 7 and Example 8 still have good cycle stability and discharge specific capacity.

[0064] Figure 4 The data graph of the cycle stability and discharge specific capacity after the positive electrode materials prepared in Example 9 and Example 10 are assembled into batteries. It can be seen from the figure that when the coating amount and the preparation process parameters change to a certain extent, the performance will fluctuate to a certain extent, but it still has good cycle stability and discharge specific capacity.

[0065] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or additions made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A sodium ion battery cathode material precursor, characterized in that: It comprises a layered hydroxide precursor and a coating layer coated on at least a part of the surface of the layered hydroxide precursor; wherein the coating layer is a Co-doped YTiTaO6 material or a Co-doped YTiTaO6 composite SrRuO3 material.

2. The sodium ion battery cathode material precursor according to claim 1, characterized in that: In Co-doped YTiTaO6, the molar ratio of Y, Ti, Co and Ta is 1:1-0.75x:x:1, 0.01≤x≤0.

1.

3. The sodium ion battery positive electrode material precursor according to claim 1, characterized in that: In the Co-doped YTiTaO6 composite SrRuO3 material, the mass ratio of Co-doped YTiTaO6 to SrRuO3 is (1~3):(1~3).

4. The sodium ion battery positive electrode material precursor according to any one of claims 1 to 3, characterized in that: The mass of the coating layer is 1-20% of the mass of the layered hydroxide precursor.

5. The sodium ion battery positive electrode material precursor according to claim 1, characterized in that: The layered hydroxide precursor is one of nickel-iron-manganese layered hydroxide, nickel-iron-copper-manganese layered hydroxide, copper-iron-manganese layered hydroxide, nickel-manganese-copper layered hydroxide, and nickel-zinc-iron-manganese layered hydroxide.

6. A method for preparing a sodium ion battery cathode material precursor according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: adding yttrium source, titanium source, cobalt source, tantalum source and complexing agent into water, stirring evenly, heating and evaporating to dryness, and further drying to obtain powder; pre-burning the powder, and then heating and calcining to obtain Co-doped YTiTaO6 powder; S2: Dispersing Co-doped YTiTaO6 powder or a mixed powder consisting of Co-doped YTiTaO6 powder and SrRuO3 powder in an alcohol solvent to obtain a dispersion; dispersing a layered hydroxide precursor in the dispersion, stirring and evaporating to obtain a solid; after the solid is dried, heating and then keeping warm under a protective atmosphere to obtain a precursor of a positive electrode material for a sodium ion battery.

7. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: In step S1, the yttrium source is one or more of yttrium nitrate, yttrium chloride, and yttrium acetate; The titanium source is one or more of butyl titanate, titanium nitrate, titanium sulfate, and titanyl sulfate; The cobalt source is one or more of cobalt nitrate, cobalt sulfate, cobalt chloride and cobalt acetate; The tantalum source is one or more of ethoxy tantalum, ammonium tantalate, and sodium tantalate; The yttrium source, titanium source, cobalt source and tantalum source are added according to the molar ratio of Y, Ti, Co and Ta being 1:1-0.75x:x:1, 0.01≤x≤0.1; The complexing agent is one or more of citric acid, urea, and polyethylene glycol, and the ratio of the molar number of the complexing agent to the total molar number of Y, Ti, Co, and Ta ions in the yttrium source, titanium source, cobalt source, and tantalum source is 1-2:

1.

8. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: In step S1, the pre-sintering temperature is 400-600°C, and the pre-sintering time is 5-8 hours; the calcining temperature is 900-1300°C, and the calcining time is 8-12 hours; In step S2, the insulation temperature is 200-400° C., and the insulation time is 0.5-5 h.

9. A sodium ion battery positive electrode material, characterized in that: The positive electrode material for a sodium ion battery is prepared by mixing the positive electrode material precursor of any one of claims 1 to 5 with a sodium source and then sintering the mixture.

10. A sodium ion battery, characterized in that: It comprises the sodium ion battery positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Positive electrode composite material for lithium ion secondary battery and use thereof

    CN110462893A

  • Sodium-ion battery precursor material, positive electrode material and preparation method

    CN115028215A

  • Multi-strategy modified cobalt-doped coated single-crystal layered oxide sodium-ion battery positive electrode material

    CN115881920A

  • Sodium ion positive electrode material, preparation method thereof and sodium ion battery

    CN116598508A

  • Positive electrode material, preparation method thereof and application of positive electrode material in sodium-ion battery

    CN116799186A